1999
DOI: 10.1159/000054423
|View full text |Cite
|
Sign up to set email alerts
|

Central Administration of Antiserum to Vasoactive Intestinal Peptide Delays and Reduces Luteinizing Hormone and Prolactin Surges in Ovariectomized, Estrogen-Treated Rats

Abstract: The present study investigated the role of hypothalamic VIP in the regulation of the LH and PRL surge using immunoneutralization of endogenous VIP in mature ovariectomized (OVX), estradiol benzoate (EB)-treated female Wistar rats. We compared the effect of intracerebroventricular (i.c.v.) injections of a VIP antiserum (VIP-Ab) with that of saline (Ctr) on LH and PRL profiles in two separate groups of rats following two subcutaneous EB injections on days 8 and 9 after OVX. VIP-Ab or Ctr injections were given du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 40 publications
(61 reference statements)
2
35
0
Order By: Relevance
“…Interestingly, Chappell et al (2000) reported that cAMP levels in the anteroventral periven-tricular nucleus (AVPV) exhibit a diurnal rhythm that is markedly analogous to the rhythm of VIP. Third, aging affects the rhythm of VIP in the SCN (Krajnak et al, 1998a), and suppression of this rhythm in young rats leads to delayed and attenuated LH surges that are strikingly similar to those observed in middleaged (MA) female rats (Harney et al, 1996;van der Beek et al, 1999).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Interestingly, Chappell et al (2000) reported that cAMP levels in the anteroventral periven-tricular nucleus (AVPV) exhibit a diurnal rhythm that is markedly analogous to the rhythm of VIP. Third, aging affects the rhythm of VIP in the SCN (Krajnak et al, 1998a), and suppression of this rhythm in young rats leads to delayed and attenuated LH surges that are strikingly similar to those observed in middleaged (MA) female rats (Harney et al, 1996;van der Beek et al, 1999).…”
Section: Introductionmentioning
confidence: 75%
“…Several lines of evidence suggest that a diurnal pattern of vasoactive intestinal polypeptide (VIP) gene and protein expression, originating from the SCN, is an essential component of the constellation of stimulatory signals leading to the proper timing of preovulatory GnRH (Harney et al, 1996;Horvath et al, 1998;van der Beek et al, 1999) and that changes in the dynamics of this neuropeptide may contribute to age-related alterations in the pattern of GnRH secretion (Krajnak et al, 2001;Le et al, 2001). First, VIP neurons in the SCN directly innervate GnRH neurons in the rostral preoptic nucleus (rMPN) (van der Beek et al, 1997;Horvath et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For example, vasoactive intestinal peptide (VIP) 2 receptors that are positively coupled to adenylate cyclase are expressed by rat GnRH neurons (36). Central administration of an antiserum to VIP delays and attenuates the LH surge (37). Overexpression of PDE4D1 could inhibit the VIP-induced increase in cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis receives strong support and the spatial analysis focused our attention on an area defined by a population of vasoactive intestinal polypeptide (VIP) neurons. VIP neurons, fibers, and receptors are found in virtually every brain region that is known to be important for social behavior (22)(23)(24)(25), but with the exception of the VIP neuronal populations in the suprachiasmatic nucleus and tuberal hypothalamus, which regulate circadian rhythms and prolactin release, respectively (26,27), we know very little about the behavioral functions of VIP cell groups and their projection systems.…”
mentioning
confidence: 99%